ASUHAN KEPERAWATAN DENGAN MASALAH DISLIPIDEMIA MELALUI SENAM AEROBIK DI WILAYAH UPT. PUSKESMAS SEI MENCIRIM - Nandari, Jesisca; Suharto, Suharto; Jundapri, Kipa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Dyslipidemia is a disorder of lipid metabolism characterized by increased levels of total cholesterol, Low Density Lipoprotein (LDL), triglycerides, and decreased High Density Lipoprotein (HDL), which can increase the risk of cardiovascular diseases. The high prevalence of dyslipidemia in the community is caused by unhealthy lifestyles, such as excessive consumption of fatty foods, lack of physical activity, and smoking habits. One non-pharmacological effort that can be applied to reduce blood lipid levels is regular physical activity in the form of aerobic exercise. This study aimed to describe family nursing care for dyslipidemia through aerobic exercise in the working area of UPT Puskesmas Sei Mencirim. The research design used was a case study with a family nursing process approach, including assessment, nursing diagnosis, planning, implementation, and evaluation. The subjects of this study consisted of two families with family members diagnosed with dyslipidemia. The results of the nursing care showed an increase in family knowledge regarding dyslipidemia, positive changes in attitudes toward a healthy lifestyle, and improvement of physical complaints such as neck pain, muscle aches, and discomfort after the regular implementation of aerobic exercise. In addition, families were able to actively participate in decision-making and in providing health care for affected family members. In conclusion, the application of aerobic exercise as part of family nursing care can improve family knowledge and involvement, as well as support the control of dyslipidemia. Therefore, aerobic exercise can be recommended as a promotive and preventive nursing intervention in community health service